Combination astragaloside IV and artesunate preserves blood–brain barrier integrity by modulating astrocytes and tight junction proteins in Plasmodium yoelii infection - Phornyupa Sanguanwong; Ladawan Khowawisetsut; Lanaprai Kwathai; Peeraporn Varinthra; Chairat Turbpaiboon; Panapat Uawithya; Prasert Sobhon; Ingrid Y. Liu; Supin Chompoopong (International Journal for Parasitology: Drugs and Drug Resistance)
Background: Astragaloside IV (ASIV), a natural compound from Astragalus membranaceus, exerts neuroprotective and anti-inflammatory effects in various pathologies. Its role in Plasmodium yoelii (Py) 17XL–induced inflammation leading to blood–brain barrier (BBB) damage remains undefined. Artesunate (ART), the frontline therapy for severe malaria, has encountered resistance and unresolved neurological sequelae. This study investigated the anti-inflammatory properties of ASIV combined with ART in Py-infected mice. Methods: Sixty-five Institute of Cancer Research mice were randomized into 5 groups: sham, Py, Py-ART, Py-ASIV, and Py-ASIV + ART. Mice in Py groups were infected with Py 17XL. Either 25 mg/kg ASIV alone or 25 mg/kg ASIV plus 2.4 mg/kg ART was administered intraperitoneally for 5 days. Survival rate/time, parasitemia, neurological status, histopathology, and biochemical indices were evaluated. Results: Although ASIV alone partially suppressed parasitemia, combination therapy significantly prolonged survival and mitigated neurological deficits. Both ASIV and ASIV + ART reduced IL-1β and TNF-α expression in serum and brain, attenuated BBB leakage (Evans blue assay), and preserved BBB integrity by decreasing astrocytic glial fibrillary acidic protein and aquaporin-4 while upregulating the tight junction proteins occludin and zonula occludens-1. Conclusions: ASIV exhibited modest antiparasitic action and robust anti-inflammatory effects, alleviating BBB disruption when combined with ART in Py 17XL–infected mice. These findings provide an essential basis for further preclinical exploration of ASIV as an adjunct therapy in severe malaria.